Contraceptive prevalence: experience from rural areas of Mymensingh - Begum, S; Haque, MM; Nasreen, SA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jul;15(2):124-7 The abstract of this article is available on the PubMed website